Food-borne zoonotic echinococcosis: A review with special focus on epidemiology - Mughees Aizaz Alvi; Abdullah F. Alsayeqh (Frontiers in Veterinary Science, 2022)
Echinococcosis is a neglected, WHO-listed cyclozoonotic parasitic disease that is caused by a number of species belonging to the genus Echinococcus. This disease is widespread across the globe, resulting in heavy economic losses for farmers and cystic disease in aberrant human hosts. This review paper briefly discussed taxonomy, a brief history, the magnitude of economic losses, host spectrum and life cycle, risk factors, and clinical manifestations. Furthermore, the copro- and sero-ELISA-based prevalence of echinococcosis on different continents was summarized. Finally, the authors analyzed the frequency and use of molecular epidemiology in the taxonomy of Echinococcus species based on molecular markers. This review will serve as a quick reference to Echinococcus.